2018
DOI: 10.3892/mmr.2018.9317
|View full text |Cite
|
Sign up to set email alerts
|

shRNA knockdown of DNA helicase ERCC6L expression inhibits human breast cancer growth

Abstract: Breast cancer is a heterogeneous disease with a high degree of diversity with regards to tumor histological stage and molecular subtypes. These heterogeneous characteristics determine the risk of disease progression and therapeutic resistance. Understanding tumor heterogeneity is of primary concern to identify and develop novel and specific potential targets for diagnosis and therapy. The present study analyzed 106 paired breast cancer tissues from The Cancer Genome Atlas and demonstrated that excision repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…ERCC6L deletion in mammalian cells can lead to cell cycle arrest, DNA damage, chromosomal abnormities, TP53 activation and apoptosis (8,33). Importantly, upregulation of ERCC6L has been identified in several cancers and is related to cancer progression and poorer prognosis of patients (5,7,(9)(10)(11). Huang et al found that ERCC6L was indispensable for the chromosome stability of cancer cells, and silencing ERCC6L could lead to apoptosis induction and proliferation inhibition of triple-negative breast cancer cells in vivo and in vitro by inducing the formation of chromatin bridges and mitotic catastrophe (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERCC6L deletion in mammalian cells can lead to cell cycle arrest, DNA damage, chromosomal abnormities, TP53 activation and apoptosis (8,33). Importantly, upregulation of ERCC6L has been identified in several cancers and is related to cancer progression and poorer prognosis of patients (5,7,(9)(10)(11). Huang et al found that ERCC6L was indispensable for the chromosome stability of cancer cells, and silencing ERCC6L could lead to apoptosis induction and proliferation inhibition of triple-negative breast cancer cells in vivo and in vitro by inducing the formation of chromatin bridges and mitotic catastrophe (7).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pu et al demonstrated that overexpression of ERCC6L in breast and kidney cancers correlated with the progression of disease and poorer survival of cancer patients (9). Huang et al showed that silencing ERCC6L in cancer cells (such as liver, breast, colorectal and kidney cancers) resulted in cell cycle arrest, proliferation inhibition, invasion reduction and apoptosis (5,7,(10)(11)(12). The above studies undoubtedly indicate the key implications of ERCC6L dysregulation in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Excision repair cross-complementation group 6-like (ERCC6L), also named as Polo-like kinase 1-interacting checkpoint “helicase” (PICH), which was identified as an embryonic development related proteins, has been shown to play critical roles in regulating the development of embryonic, brain and other tissues [ 6 8 ]. Recently several reports revealed that abnormal ERCC6L expression has been detected in several malignant solid tumors consisting of breast cancer [ 9 ], kidney cancer [ 10 ], and neuroblastoma [ 11 ]. In addition, high ERCC6L expression level is related to poor prognosis in breast cancer patients, and may regulate cell proliferation, invasion and metastasis by regulating different single pathways.…”
Section: Introductionmentioning
confidence: 99%
“…VNTR 945060 is in the 5’UTR of ERCC6L , a DNA helicase. ERCC6L is highly expressed in breast tissue and higher levels of expression have been associated with worse survival [33]; silencing of ERCC6L in breast cell lines significantly inhibited cell proliferation [33, 34]. A second VNTR, 253688, is located 3’ of FLJ22447 , a lncRNA located near HIF-1α .…”
Section: Discussionmentioning
confidence: 99%